Método e métodos do pensamento filosófico - Diogo Ferrer (Documentos, 2007)
The conference of the Coimbra Philosophical Journal entitled "Method and Methods of Philosophical thought" was held on 27th and 28th April 2006 at the Institute of Philosophical Studies, Faculty of Letters, University of Coimbra. The conference proceedings cover the problem of the method of philosophy in various historical and systematic contexts since Plato. This work brings together different approaches to a theme that is fundamental for the whole of philosophical thought, whether one is positioning oneself as a detached observer of any method, or vindicating autonomy before the very concept of method. From the dialectic, transcendental, phenomenological, hermeneutic, analytic, conceptual history or systems theory perspectives, this work reflects about what one is doing when one philosophizes and how the object of thought is pursued when a philosophical problem is studied systematically, (i.e., the very "know yourself" of philosophy). This plural reflection on methods of philosophical thought launches a special series of the Coimbra Philosophical Journal.